Assessing Fertility Behaviours In Manipur: Examining The ’Hills’-’Plains’ Dichotomy - Chanu, Naorem Pushparani; Elangbam, Rabichandra Singh (Migration Letters, 2024)
The latest data from the National Family Health Survey (NFHS-5) indicates that the total fertility rate (TFR) of Manipur is close to replacement level, standing at 2.2 children per woman. However, there’s a notable contrast in TFR between the ’hill’ and ’plain’ regions within the state, which forms the major focus of this paper. Our study has two main objectives: firstly, to discern the determinants of TFR in Manipur and their divergence between the ’hills’ and ’plains’; and secondly, to examine whether a preference exists for a specific sex of a child and its impact on a mother’s future fertility intentions. Utilizing two econometric models—multiple linear regression and multinomial logistic regression—we reveal that TFR in the ’hill’ regions exceeds replacement levels, while the ’plain’ regions fall below. Furthermore, socio-demographic factors play a significant role in shaping the total fertility of a mother. Our study identifies that the preference for daughters exists, albeit to a lesser extent than for sons. The presence of at least one son in the family decreases women’s future fertility intentions in Manipur.